Study Deskriptif Faktor-Faktor Penunjang Dan Penghambat Pengembangan Kecerdasan Moral Anak Usia Dini 5-6 Tahun - Ari Sofia; Nopiana Nopiana; Suryadi Suryadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2021)
The purpose of this study is to find out the knowledge and understanding of kindergarten teachers about moral intelligence, especially the supporting and inhibiting factors for its development. Because the existing knowledge and understanding can be the basis for teachers in stimulating the development of children's moral intelligence. The design used a quantitative descriptive method, with test data collection techniques. This research was conducted from April to September 2018. Involving 22 teachers from 13 Kindergartens in Bandar Lampung. The results showed the teacher understood enough about the understanding of moral intelligence, what factors were supporting the development of children's moral intelligence, what factors were inhibiting the development of children's moral intelligence, the things teachers had done to develop children's moral intelligence at school and how parental involvement in developing children's moral intelligence at school. However, a sufficient understanding of the teacher cannot guarantee the development of children's moral intelligence properly. A good level of understanding is still needed so that the development of children's moral intelligence can develop more optimally.